Targeting of Development Programs: A case study comparing PMT score targeting with community based targeting - Mahmoud, Mai (International Food Policy Research Institute, 2023)
This video features a presentation by Mai Mahmoud, a PhD Candidate in Economics and Public Policy at the Fletcher School, Tufts University. She served as the keynote speaker at the Bridging Evidence and Policy (BEP) Seminar Series held on October 2, 2023, at Conrad Cairo, Egypt. The BEP Seminar Series is part of the CGIAR Research Initiative on National Policies and Strategies.